Assessment of the Jati Besar Highway of the City of South Ternate Uses Pavement Condition Index (PCI). Issue 1 (May 2021) - Sabaruddin,; Tata, Arbain
Abstract: Jati Besar Ternate road has a width of 7, 00 m a type of road with 1/2 UD which has function which functions as a secondary gathering path.. To determine the condition of pavement of the Great Jati road used Pavement Condition Index (PCI) assessment method.. The results showed that the overall condition of road pavement in both good and perfect categories. Types of damage that found in the was road consists of alligator cracking 0, 83 %; shoving 0, 17%; edge cracking 0, 06 %; longitudinal cracking 0, 27 %; patching 0, 39%; potholes 0, 18 %; The average PCI value of Segment total was 97.85 with excellent condition. The type of maintenance required on road of Jati Besar was routine maintenance.